2007
DOI: 10.1159/000106316
|View full text |Cite
|
Sign up to set email alerts
|

The <i>GSTP1</i> Gene Is a Susceptibility Gene for Childhood Asthma and the <i>GSTM1</i> Gene Is a Modifier of the <i>GSTP1</i> Gene

Abstract: Background: Bronchial asthma is a chronic airway disorder characterized by bronchial inflammation. Oxidative stress is a key component of inflammation. Glutathione S-transferase P1 (GSTP1), the abundant isoform of glutathione S-transferases (GSTs) in lung epithelium, plays a key role in cellular protection against oxidative stress. Several studies have shown that the GSTP1 geneis involved in the pathogenesis of asthma and a gene-gene interaction may occur within the GST gene superfamily. Methods: We screened s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 82 publications
1
27
1
2
Order By: Relevance
“…This is consistent with our observations that GSTP1 Val105 allele carriers had an increased risk of developing AD. However, many reports have shown that the Val105 allele is associated with a decreased risk of allergic asthma (12,13), although some studies reported that the Val105 allele actually increased the risk of asthma (14,16). The GSTP1 Ile105Val polymorphism was not significantly associated with aspirin-intolerant asthma in Koreans (28).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This is consistent with our observations that GSTP1 Val105 allele carriers had an increased risk of developing AD. However, many reports have shown that the Val105 allele is associated with a decreased risk of allergic asthma (12,13), although some studies reported that the Val105 allele actually increased the risk of asthma (14,16). The GSTP1 Ile105Val polymorphism was not significantly associated with aspirin-intolerant asthma in Koreans (28).…”
Section: Discussionmentioning
confidence: 90%
“…Second, the frequencies of the Val105 allele in Asians are much lower than those of other ethnicities, which may explain the conflicting findings. For example, the Val105 allele decreased the risk of asthma in Northern Europeans for which the Val allele frequency is 47.7% (12), whereas the Val105 allele increased the risk of asthma in the Japanese population for which the Val allele frequency is 13.4% (14). Studies in Taiwanese individuals (Val allele frequencys25.3%) (15) have shown that the Ile105 homozygosity was related to an increased risk only in areas with high air pollution, and no association was found in areas with low air pollution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these multi-site genes, 3 are of particular interest: CHRM1, as it was the top result among 10% b-diff results; ESM1, a gene mainly expressed in the endothelial cells in human lung and kidney tissues 27 ; and PITPNM1, a gene found within a linkage disequilibrium block surrounding the susceptibility gene identified in a previous association study of childhood asthma. 28 The ESM1 result provides a compelling demonstration of COPD-related gene regulation through hypermethylation in the cases, and concomitant reduction in gene expression. Although the ESM1 sites fall within the first exon for a majority of the transcripts, and this location (downstream of the transcription start site) would predict a positive correlation between gene expression and methylation, 29 other transcripts are also annotated to the 5 0 UTR, where anti-correlation could be expected.…”
Section: Discussionmentioning
confidence: 99%
“…There are known two polymorphisms of GSTP1: substitution of isoleucine to valine at amino acid 105 and alanine to valine at amino acid 114, demonstrating different catalytic efficiencies due to changes in the active site (Ali-Osman et al, 1997). A number of studies suggest that GSTM1, GSTT1, GSTM1 polymorphisms increase susceptibility to asthma Hanene et al, 2007;Kamada et al, 2007;Romieu et al, 2006;Tamer et al, 2004). GSTM1 and GSTT1 deficiency may increase the risk for the asthma development of in utero and current smoke exposure .…”
Section: Genetic Changes In Bronchial Asthma Related To Oxidative Damagementioning
confidence: 99%